Internal and External Factors Influencing Students’ Reluctance to Speak English - Maria Elsa Maharrani; Bunga Ayu Wulandari; Nely Arif (Penerbit Hellow Pustaka, 2025)
The aim of this research to investigated the factors that most influenced the tenth-grade students of SMAN 12 Kota Jambi’s reluctance to speak English. This research utilized a quantitative method with a survey approach. The data of this research were collected by using a questionnaire The results showed that internal factors had a mean value of 33.99, while external factors had a mean value of 25.69. Based on these data, it can be informed that internal factors had the highest mean value, which means that internal factors caused higher reluctance than external factors. Among internal factors, the fear of mistakes was the most influential on the tenth-grade students of SMAN 12 Kota Jambi's reluctance to speak English, because it had the highest mean value, 3.34. Therefore, support from the students’ environment is needed, for example, motivation from their parents and positive support from their classmates. The teachers should advise the use of appropriate learning techniques. Additionally, students should be given an understanding that making mistakes is normal in the learning process.